Manganese Removal Status by Arsenic Removal Technologies Available in Bangladesh: Manganese Removal Treatment by Sodium Hypochlorite - Siraj, S; Kazi, AI; Ahmed, S; Akbor, MA; Ahsan, A (Bangladesh Journal of Scientific and Industrial Research, 2011)
In addition to arsenic, the groundwater in Bangladesh is often found to be contaminated with manganese whose permissible limit set by WHO being 400 ppb in drinking water. Since most arsenic removal technologies (ARTs) are designed to remove As and not to remove Mn, during field testing and verification of performance of ARTs under the Bangladesh Environmental Technology Verification-Support to Arsenic Mitigation (BETV-SAM) project of BCSIR, it has been found that only the Sono technology using Fe0 as arsenic removal medium which can also remove Mn to produce Mn safe drinking water but others such as Alcan, Read-F household, Sidko, Nelima, Shawdesh cannot. During field testing of these technologies under the BETV-SAM project, it has been attempted to treat Mn by a traditional chlorine oxidation method to produce Mn safe drinking water. Concentrations of dissolved As (T), As (III), Fe, Mn and pH in the considered well water for manganese treatment were in ranges of 125 - 1247 ppb, 116 - 1127 ppb, 1.40 - 15.5 ppm, 505 - 2245 ppb and 7.0 to 7.5, respectively. The required chlorine dose and time for treatment of manganese in 20 L water have been found to be 6.2 - 12.4 ppm and 1 - 2 h, respectively. Keyword: Arsenic; Manganese; ART; Verification; Chlorine; Iron. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9033 BJSIR 2011; 46(3): 291-296